Indicators of regional high capacity well impacts predicts fen floristic quality and composition in Wisconsin calcareous fens. (February 2022) - Bart, David; Loheide, Steven; Booth, Eric G.
Abstract: High-capacity wells (HCWs) are known to reduce groundwater discharge to fens and impact their floristic quality, but whether HCW impacts have become predictive of fen floristic quality across large areas has not been studied. Here we used Thiem-equation-estimated drawdown as an indicator of regional HCW impacts to predict floristic quality, floral richness, and community composition in fens throughout their Wisconsin (USA) range. This indicator of HCW influence (HCWinfluence ) was associated with a strong decline in floristic quality measures and native-species richness, while non-native-species richness increased sharply. Fuzzy Set Ordination of community data suggested estimated drawdown was associated with the loss of high coefficient-of-conservatism graminoids and forbs, specialist species, and state-listed rare species. The abundance of non-native species and weedy natives increased with increasing HCW impact. The fact that our indicator of HCW influence has become predictive of fen quality and community composition statewide suggests that HCWs are a driver of floristic quality across large areas, and that possible declines in fen quality due to cumulative impacts should be addressed before siting wells. Highlights: We compared floristic quality in a statewide sample of WI fens with indicators of regional high capacity well impacts. Floristic quality and richness of rare species are lower where impact is greater. Richness and cover of non-native species increase with increasing estimated impacts. High-capacity well impacts may now drive fen quality over large areas.